EDUKASI ANIMASI KANKER SERVIKS MENINGKATKAN MINAT WANITA USIA SUBUR TERHADAP PEMERIKSAAN IVA - Dini Fitri Damayanti; Dianna; Anggraini Mutia (WOMB Midwifery Journal, 2023)
The low achievement of the target of the visual acid acetate injection examination (IVA) suggests that women of fertile age (WUS) still get little education about cervical cancer. The use of pocketbook media did not show the achievement of IVA inspection targets. The aims to know the impact of cervical cancer animation education on the increased interest of WUS in conducting IVA examinations in Puskesmas Pal Lima. The Method is quasi-experimental research was carried out from April to May 2022 in the UPT Puskesmas Pal Lima work area. The large sample for the research was 30 subjects obtained from the Lameshow formula. Interest scores before and after cervical cancer animation education were measured using a questionnaire of 20 questions. Data analysis using a pair-t test The results of this study showed that giving cervical cancer animation education increased WUS interest in IVA examinations (p = 0,007). The interest score increased by 6.37. Cervical cancer education using animated videos can be used as a midwife to increase WUS interest in IVA examination. Cervical cancer education with audiovisual animation is more efficiently accepted by society than pocket books.